Odkrivanje sindroma fragilnega kromosoma X na osnovi tehnologije PCR pri moški populaciji iz severovzhodne Slovenije - Kunčnik, Vesna (Slovenska pediatrija, 2012)
Background. Fragile X syndrome (FXS) is the most common cause of inherited mental retardation in males. It's caused by an unstable expansion of a trinucleotide CGG repeat in the FMR1 gene on chromosome X. The definitive diagnosis of FXS is based on molecular genetic analysis, using the Southern blot tehnique, which is a demanting and time-consuming tehnique. In this study we present a diagnostic strategy based on PCR assay, designed as an exclusion test for detection of the FMR1 mutation. We present the results of a retrospective analysis in agroup of male subjects from NE Slovenia. Methods. We present a retrospective study of 104 male subjects with the following referral diagnoses: suspected FXS,unexplained mental retardation or dysplastic signs with/without autism.The cause of their disability had not been revealed by previous diagnostic tests. We performed PCR analysis of genomic DNA extracted from the peripheral blood of subjects. Using the PCR technique and agarose electrophoresis we determined the presence/absence of the normal number of repeats of the CGG triplet in the FMR1 region. Results. The PCR method was successful in 99 of 104 subjects. In five of the 104 samples (4,81%) no results could be obtained because of bad DNA quality. The presence of normal CGG sequence variations was detected in 98 subjects. In one subject (1,01%, 1/99) we established the suspicion of FXS, which was subsequently confirmed by Southern blot analysis. Conclusions. The presented methodology based on PCR assay is suitable as a preliminary test to exclude FXS in male subjects. Using this approach we detected the full mutation in 1.01% of male subjects with suspected FXS.
Keywords: Abnormalities; Diagnosis; Diagnostika; Duševna manjrazvitost; duševne motnje; Fragile X Syndrome; Fragilni X sindrom; Genetics; Genetika; Kromosom X; Mental Retardation; Nepravilnosti; Reverse Transcriptase Polymerase Chain Reaction; sindrom fragilnega kromosoma; Verižna reakcija s polimerazo; X Chromosome